The Existence of Online Trials (Electronic Court) in Civil Cases in Medan State Court, Indonesia - Nababan, Roida; Habeahan, Besty; Siregar, Hisar; Simanjuntak, Frans Marcelino (Golden Ratio of Law and Social Policy Review, 2025)
Civil law governs the rights and obligations of citizens, encompassing both material and procedural regulations. To improve access to justice, the Supreme Court introduced an online trial system (e-court) in 2018, which was implemented nationwide in 2020. Online trials provide several advantages, including ease of access, cost and time efficiency, and enhanced data security. Despite these benefits, several challenges persist. In Indonesia's eastern regions, internet connectivity remains a significant barrier. Additionally, the implementation of online trials can be less than ideal, with frequent audio disruptions hindering the extraction of case facts. Other obstacles include limited technological proficiency among users, inadequate coordination between involved parties, and challenges ensuring the safety and honesty of witnesses and defendants. Public education is also necessary to maximize the potential of the e-court system. Awareness campaigns can help citizens understand how to utilize this technology effectively, such as registering cases online through the court's official website.